2002
DOI: 10.1110/ps.021860
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a fluorescent biosensor family

Abstract: Bacterial periplasmic binding proteins (bPBPs) are specific for a wide variety of small molecule ligands. bPBPs undergo a large, ligand-mediated conformational change that can be linked to reporter functions to monitor ligand concentrations. This mechanism provides the basis of a general system for engineering families of reagentless biosensors that share a common physical signal transduction functionality and detect many different analytes. We demonstrate the facility of designing optical biosensors based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
193
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(200 citation statements)
references
References 85 publications
7
193
0
Order By: Relevance
“…The mechanism for the two dual-labeled NBD-TR CCS proteins appears to result primarily from the large change in fluorescence intensity upon glucose binding of the environment-sensitive donor fluorophore NBD at the E149C site 11 as well as a modest contribution from distancedependent FRET between NBD and TR. The absorbance spectra of NBD for both NBD-TR C2 CCS and NBD-TR C5 CCS (Figure 3) do not indicate that any ground state perturbation of NBD is occurring, unlike the case of doubly labeled 2NBD CCS, in which a significant blue shift is observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism for the two dual-labeled NBD-TR CCS proteins appears to result primarily from the large change in fluorescence intensity upon glucose binding of the environment-sensitive donor fluorophore NBD at the E149C site 11 as well as a modest contribution from distancedependent FRET between NBD and TR. The absorbance spectra of NBD for both NBD-TR C2 CCS and NBD-TR C5 CCS (Figure 3) do not indicate that any ground state perturbation of NBD is occurring, unlike the case of doubly labeled 2NBD CCS, in which a significant blue shift is observed.…”
Section: Discussionmentioning
confidence: 99%
“…13,22 The potential of GGBP for in vivo blood glucose monitoring has been frequently suggested. 10,11,23,24 A prototype continuous glucose fiber optic sensor based on GGBP was evaluated in preclinical studies, 25 and the sensor has further demonstrated competitive accuracy in a human feasibility study. 26 The GGBP in the prototype sensor was labeled with a single environment-sensitive fluorophore, acrylodan.…”
Section: Introductionmentioning
confidence: 99%
“…They found a increase in fluorescence intensity of 1.8-fold with their sensor. Hellinga and coworkers studied this kind of biosensor in detail, both with MBP and with their derivative that binds zinc (de Lorimier et al, 2002, Hellinga & Marvin, 1998, Marvin & Hellinga, 2001). They mutated a number of MBP residues to cysteine, then tested a number of fluorescent dyes to find the best combination of position and dye.…”
Section: Fluorescent Biosensors With a Single Fluorescent Reportermentioning
confidence: 99%
“…The family of periplasmic binding proteins (PBPs) that presented a conformational change upon ligand binding has been used to create diverse biosensors based in the fluorescent incorporation by chemical modification with thiol-fluorescent reactive for cysteine. This work has been pioneered by Cass and col by introduction of fluorescent group into the maltoside binding protein (MBP) a PBP, and extensively developed by Hellinga and collaborators (de Lorimier, Smith et al 2002). This family of proteins presented a bilobated structure with high similarity, that present at least two conformers: an open form in absence of ligand and a closed state bound to its ligand (Fig.…”
Section: Biosensors For Protein-ligand Based In Conformational Changesmentioning
confidence: 99%